"SET" for Success: Targeted Instruction in Learning Strategies and Behavior Change in Introductory Psychology. (July 2021) - McCabe, Jennifer A.; Friedman-Wheeler, Dara G.; Davis, Samuel R.; Pearce, Julia
Background: Undergraduates may not use the most effective learning strategies, particularly those considered "desirable difficulties" such as spacing, elaboration, and testing ("SET"). Objective: This study examined knowledge-based, metacognitive, and behavioral outcomes from interventions designed to teach undergraduates about the "SET" strategies and about behavior change techniques to support adoption of these study behaviors. Method: Introductory psychology students ( n = 244) received a learning-strategies-only intervention (LS), a learning-strategies-plus-behavior-change (LS+BC) intervention, or no intervention. They completed three assessment surveys to measure outcomes across the semester. Results: Intervention participants showed enhanced knowledge of the "SET" strategies. LS participants rated testing as more helpful, reported higher use of elaboration and testing, and had marginally higher final course grades than the control group. Adding behavior-change training did not enhance the outcomes. Growth mindset was associated with greater intervention-related gains on several measures. Conclusion: Curriculum-embedded LS training was associated with positive shifts in "SET" strategy knowledge and with behavioral changes for two strategies. Teaching Implication: This study provides evidence of the benefits of LS training as integrated into the introductory psychology curriculum, and can help guide educators to support students in acquiring more effective study strategies.